2016
DOI: 10.4315/0362-028x.jfp-15-581
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Digestion for Improved Bacteria Separation from Leafy Green Vegetables

Abstract: An effective and rapid method for the separation of bacteria from food matrix remains a bottleneck for rapid bacteria detection for food safety. Bacteria can strongly attach to a food surface or internalize within the matrix, making their isolation extremely difficult. Traditional methods of separating bacteria from food routinely involve stomaching, blending, and shaking. However, these methods may not be efficient at removing all the bacteria from complex matrices. Here, we investigate the benefits of using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This approach has been very effective when treating meat and egg products, and may have the potential same effect when treating plant related extracts, for degradation of polymeric sugars, proteins etc, especially when using harsher mechanical treatment (blender, stomacher), although this needs to be validated further. Our initial data indicate that enzymes with potential for biofilm disintegration including plant cell wall degrading enzymes such as cellulases, hemicellulases, pectinases do not affect microbial viability, in agreement with the literature (Wang et al, ).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…This approach has been very effective when treating meat and egg products, and may have the potential same effect when treating plant related extracts, for degradation of polymeric sugars, proteins etc, especially when using harsher mechanical treatment (blender, stomacher), although this needs to be validated further. Our initial data indicate that enzymes with potential for biofilm disintegration including plant cell wall degrading enzymes such as cellulases, hemicellulases, pectinases do not affect microbial viability, in agreement with the literature (Wang et al, ).…”
Section: Introductionsupporting
confidence: 92%
“…can be used to degrade the biofilm matrix (Furukawa et al, ; Lequette et al, ), and a mixture of them is generally necessary due to the variety of polymers composing the matrix. Wang et al (), recently reported that enzyme digestion (using cellulase and pectinase commercial enzyme preparations) improved separation of bacteria (in this case, Salmonella ) and recovery from leafy green vegetables. They report the enzymes did not affect microbial viability and the resultant extract did not have significant antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…are established as effective degraders of similar cellulosic wastes for the production of bioethanol, which may have a crucial role in fulfilling current and future energy demands [ 4 ]. In some recent studies, cellulases have been evaluated successfully for decontaminating the cellulosic biofilm-forming microbes like Salmonella spp., when used in processing vegetables and meat [ 5 , 6 ]. In a similar study, cellulases have been used to improve the feedstock for broiler chickens [ 7 ].…”
Section: Introductionmentioning
confidence: 99%